The tourist as a metaphor of the social world - Dann, G. M. S.; Dann, G. M. S. (Wallingford :CABI Publishing, 2002)
This book includes 15 papers selected from the presentations that were delivered at the 15th World Congress of the International Sociological Association. These papers were prepared for that organization's research committee on international tourism, which took as its overall theme 'the tourist as a metaphor of the social world'. Following the introductory chapter, two contributions (chapters 2 and 3) raise serious fundamental questions about how academics should research (and hence theorize) about tourists. The next two contributions (chapters 4 and 5) provide a critique of conventional tourism wisdom. Chapter 6 suggests that tourism is an intricate and evolving social network with varying degrees of trust that are based on the correlative processes of self-presentation and interpretation. Chapter 7 conceptualizes the tourist and the social world within a paradigm of social facts so that the former becomes a sign of the latter. Chapter 8 sees the tourist as never entirely alone on an uncharted journey, because there are always those who have undertaken it before. Chapter 9 asks the question as to whether or not tourists experience reality. Chapter 10 provides an analogy between tourism and love in all its many phases. Chapter 11 emphasizes that it is necessary to go beyond traditional analyses that focus solely on the 'tourist gaze'. The next two essays (chapters 12 and 13) highlight the fact that not all tourists are identical and hence, by implication, that the tourist as a metaphor of the social world must be understood as a multiple persona figurative of complex reality. The final three contributions (chapters 14-16) present postmodern and futuristic perspectives on tourists. The book has a subject index.
Keywords: UU485 - Social Psychology and Social Anthropology, (New March 2000); UU700 - Tourism and Travel